Supplementing organic-complexed or inorganic Co, Cu, Mn, and Zn to beef cows during gestation: physiological and productive response of cows and their offspring until weaning - Harvey, Kelsey M.; Cooke, Reinaldo F.; Colombo, Eduardo A.; Rett, Bruna [UNESP]; Sousa, Osvaldo A. de [UNESP]; Harvey, Lorin M.; Russell, Jason R.; Pohler, Ky G.; Brandao, Alice P. (Oxford Univ Press Inc, 2021)
One hundred and ninety non-lactating, pregnant beef cows (three-fourth Bos taurus and one-fourth Bos indicus; 138 multiparous and 52 primiparous) were assigned to this experiment at 117 +/- 2.2 d of gestation (day 0). Cows were ranked by parity, pregnancy type (artificial insemination = 102 and natural service = 88), body weight (BW), and body condition score (BCS) and assigned to receive a supplement containing: 1) sulfate sources of Cu, Co, Mn, and Zn (INR; n = 95) or 2) an organic-complexed source of Cu, Mn, Co, and Zn (AAC; Availa 4; Zinpro Corporation, Eden Prairie, MN; n = 95). The INR and AAC provided the same daily amount of Cu, Co, Mn, and Zn, based on 7 g of the AAC source. From day 0 to calving, cows were maintained in a single pasture and were segregated three times weekly into 1 of the 24 individual feeding pens to receive treatments. Cow BW and BCS were recorded on days -30, 97, upon calving, and at weaning (day 367). Milk production was estimated at 42 +/- 0.5 d postpartum via weigh-suckle-weigh (WSW) method. Liver biopsies were performed in 30 cows per treatment on days -30, 97, upon calving, and the day after WSW. Calf BW was recorded at birth and weaning. Liver and longissimus muscle (LM) biopsies were performed in 30 calves per treatment upon calving and 24 h later, the day after WSW, and at weaning. No treatment effects were detected (P >= 0.49) for cow BCS during gestation, despite AAC cows having greater (P = 0.04) BW on day 97. Liver Co concentrations were greater (P < 0.01) for AAC compared with INR cows, and liver concentrations of Cu were greater (P = 0.02) for INR compared with AAC cows on day 97. Upon calving, INR cows had greater (P <= 0.01) liver Cu and Zn concentrations compared with AAC cows. No other treatment differences were noted (P >= 0.17) for cow and calf liver trace mineral concentrations. Cows receiving AAC had greater (P = 0.04) hepatic mRNA expression of metallothionein 1A at calving, and their calves had greater (P = 0.04) hepatic mRNA expression of superoxide dismutase at weaning. Milk production did not differ between AAC and INR cows (P = 0.70). No treatment effects were detected (P >= 0.29) for mRNA expression of LM genes associated with adipogenic or muscle development activities in calves at birth and weaning. Calf birth and weaning BW also did not differ (P >= 0.19) between treatments. In summary, supplementing AAC or INR to beef cows during the last 5 mo of gestation yielded similar cow-calf productive responses until weaning.
Keywords: beef cows; gestation; offspring; physiology; production; trace minerals